Vijf van de zeven schrijvers van "Tien over Rood". V.l.n.r.: Lammers, Van den Doel, De Rooi, Van der Zwan en Van der Hek - Peeterse, Jan H.,
Vijf van de zeven schrijvers van "Tien over Rood". V.l.n.r.: Lammers, Van den Doel, De Rooi, Van der Zwan en Van der Hek.